Psiconutrición, prevalencia de anemia y estado nutricional en adolescentes mujeres de la Institución Educativa N° 60128, Peña Negra, San Juan Bautista, 2022 - Lachi Vargas, Ruth Isabel (2023)
In this present research, the relationship between psychonutrition with nutritional status and the prevalence of anemia in female adolescents was evaluated. Institucion Educativa N°60128, Peña Negra, San Juan Bautista. A survey was conducted on psychonutrition, anthropometric data, nutritional status, and hemoglobin level in 71 female adolescents. A quantitative, non-experimental, descriptive, correlational and cross-sectional approach was carried out on female adolescents. Most of the adolescents had values lower than 11.0 mg/dl. 51% of female adolescents had low height for their age. Adequate abdominal perimeter values were observed. They also had a low or low severe emotional measurement scale. The survey was confidential where each student had a number. Among the results, the abdominal perimeter was notable in the Low range with 47%. Therefore, it was concluded in a satisfactory manner, so I had the support and collaboration for the data collection of the students, where they showed effort and gratitude so that everything was good and in order. Where it is a very influential role to proceed with the research, also with the acceptance of the I.E. No. 60128. As the director and teachers agreed to our request.